2019
DOI: 10.1063/1.5117159
|View full text |Cite
|
Sign up to set email alerts
|

Optomechanical spring enhanced mass sensing

Abstract: On-chip nano-optomechanical systems (NOMS) have demonstrated a zeptogram-level mass sensitivity and are promising candidates for low-cost implementations in areas such as metabolite quantitation and chemical analysis. High responsivity and sensitivity call for substantial optomechanical coupling and cavity finesse, resulting in detuning-dependent stiffness and mechanical damping via optomechanical back-action. Since mass loading (or temperature or force change) can alter both mechanical and cavity properties, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…However, thermo-optical noise caused by the instability of coupling methods, for example tapered fiber coupling, limits their sensing resolution to the level of picograms. To reduce this noise, the integrated bus waveguide [133] coupling may be an alternative and effective scheme. For PhC cavities based optomechanical mass sensors, most research has focused on the numerical analysis [134][135][136], as shown in Figure 22a.…”
Section: Mass Sensingmentioning
confidence: 99%
“…However, thermo-optical noise caused by the instability of coupling methods, for example tapered fiber coupling, limits their sensing resolution to the level of picograms. To reduce this noise, the integrated bus waveguide [133] coupling may be an alternative and effective scheme. For PhC cavities based optomechanical mass sensors, most research has focused on the numerical analysis [134][135][136], as shown in Figure 22a.…”
Section: Mass Sensingmentioning
confidence: 99%
“…The disk combines an experimental mass detection limit of 40 MDa with a capture area of 380 μm 2 , two decades above recent realizations. 11,12,14 We demonstrate dual mechanical and optical sensing, as well as multimode mechanical sensing, obtaining multiple concomitant informations on the deposited particles in real time. The optomechanical device is optimized to weight masses up to tens of GDa, and we were able to measure and quantitatively analyze the deposition of individual nanoparticles that mimic intermediate viruses, be it by their size and mass (150 nm diameter nanoparticles) or by their elastic modulus (soft latex nanoparticles).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among them, all-optical techniques bring about a wide-band and low-noise-actuation capacity, together with an outstanding sensitivity to mechanical motion, which are central advantages in working with high-frequency resonators of small size. Such optical techniques naturally benefit from optomechanical concepts, , and miniature optomechanical resonators were recently investigated for the mechanical sensing of objects of nanoscale mass, with an improving level of control. This culminated in ref , where single-particle nanomechanical mass spectrometry in the megadalton range was demonstrated using an optomechanical nanoram device with a capture area of 4.5 μm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The latter mode is particularly interesting since it is resilient to low‐frequency noise. It has been widely employed in many areas, ranging from force [ 6 ] and mass sensing, [ 11,12 ] inertial sensing, [ 7,13,14 ] electro‐ [ 15 ] and magnetometry, [ 8 ] acoustic sensing, [ 16–18 ] atomic force microscopy, [ 19 ] refractive index sensing, [ 20 ] and chemical and bio‐sensing for tracking chemical reactions and molecular dynamics. [ 21–23 ] Most sensing experiments make use of feedback control such as the Pound–Drever–Hall (PDH) technique [ 24 ] to lock the laser to the cavity mode.…”
Section: Introductionmentioning
confidence: 99%